Internet: A Homeland in Common - M. Tayfun Gülle (Türk Kütüphaneciliği)
In the Editorial part of this issue, brief information is given about the problems facing internet usage in Turkey, which is spreading day by day. It is emphasized that the laws made for disciplining the internet in Turkey through legal regulations affect both the violators and the innocent, leading to a restriction in the society’s access to information and freedom of expression. Departing from the argument that people, societies, regions and countries can freely exhibit their different cultural and social structures through the internet, which will lead to the proliferation of tolerance among world people, the Editorial emphasizes that there is a need for a legal regulation to punish the real violators instead of disciplining this cyber world which has turned into a “homeland in common.”